Burning mouth syndrome – known and unknown - Zlatina Tomova; Atanas Chonin; Radka Cholakova; Iliyana Stoeva (Folia Medica)
The aim of this literature review was to provide a brief perspective over the scientific research of the condition known as burning mouth syndrome. Information from review articles, original studies, and dissertations was gathered using keywords describing etiological factors, clinical, laboratory findings and treatment protocols. We compiled information on potential etiological factors, symptoms, and potential treatments from the fifty-three included studies on dental and general health issues in patients complaining of burning sensations in their mouths. Despite the numerous attempts by dental and medical professionals to diagnose and treat mouth burning, the etiology and pathogenesis of this disorder remain rather unclear. In most cases, it is concluded that further research is needed with the inclusion of more patients, administering a long-term therapy, and monitoring the results.